(untitled) (Innovative professional education, 2025)
This study examines the features of quality assurance in vocational education and training in the Kingdom of the Netherlands, which is based on a well-defined legislative framework, including laws on compulsory education, adult education and vocational-technical education, higher vocational education, and scientific research. The role of institutional mechanisms for quality control and accreditation of vocational education and training programs in accordance with quality standards is described